Enhancing Customer Loyalty in State-Owned Logistics Providers: The Role of Operational Excellence, Information Quality, and Digital Transformation - Maya Irjayanti; Anton Mulyono Azis; Reza Ibrahim Ramadinka (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
This study investigates the concerning decline in the logistics service quality of state-owned logistics service providers in Indonesia, as indicated by the 2023 Logistics Performance Index (LPI). An Indonesian state-owned logistics company is presently ranked 9th in usage frequency, behind its domestic competitors. This study aims to identify the critical components encountered by state-owned logistics service provider and investigate the transformation initiatives implemented to improve their operations. A mixed-method approach utilized in this study, incorporating quantitative data from 199 respondents analyzed using the Smart Partial Least Squares (PLS) technique, with qualitative data from Focus Group Discussions and secondary data. The results indicate that service quality is a pivotal factor influencing customer satisfaction and loyalty. Many operational issues were uncovered, highlighting previous challenges that led to the company's collapse. This study indicates the strategic transformations implemented to regain competitiveness, encompassing enhancements in service processes and innovations focused on customer needs. Practical ideas are offered to improve service performance, enabling state-owned logistics service providers to maintain customer trust and attain long-term success in an increasingly competitive market. Further, this research contributes to the discussion regarding sustainability by advocating for logistics practices that are efficient, reliable, and customer-centric, which are conducive to the long-term resilience of organizations. These transformations are consistent with the objectives of Sustainable Development Goal 9 (Industry, Innovation, and Infrastructure) by promoting innovation in public service delivery and improving infrastructure. Also, the promotion of sustainable logistics operations that reduce inefficiencies and waste is a way in which the emphasis on service quality and operational enhancements contributes to Goal 12 (Responsible Consumption and Production).